Observations of Nutrient Supply by Mesoscale Eddy Stirring and Small-Scale Turbulence in the Oligotrophic North Atlantic - Spingys, Carl P.; Williams, Richard G.; Tuerena, Robyn E.; Naveira Garabato, Alberto; Vic, Clément; Forryan, Alexander; Sharples, Jonathan (Global Biogeochemical Cycles, 2021)
International audience Sustaining biological export over the open ocean requires a physical supply of nutrients to the mixed layer and thermocline. The relative importance of diapycnal mixing, diapycnal advection, and isopycnal stirring by mesoscale eddies in providing this nutrient supply is explored using a field campaign in oligotrophic waters in the subtropical North Atlantic, consisting of transects over and off the mid-Atlantic ridge. Eddy stirring rates are estimated from the excess temperature variance dissipation relative to the turbulent kinetic energy dissipation, and using eddy statistics from satellite observations combined with 9-month-long mooring data. The vertical nutrient fluxes by diapycnal mixing, diapycnal advection, and isopycnal mesoscale eddy stirring are assessed using nitrate measurements from observations or a climatology. Diapycnal mixing and advection provide a nutrient supply within the euphotic zone, but a loss of nutrients within the upper thermocline. Eddy stirring augments, and is comparable to, the diapycnal transfer of nutrients within the summertime upper thermocline, while also acting to replenish nutrients within the deeper parts of the thermocline. The eddy supply of nitrate is relatively small in the center of the subtropical gyre, reaching up to 0.06 mol N m -2 yr -1 , but is likely to be enhanced on the flanks of the gyre due to larger isopycnal slopes and lateral nitrate gradients. The nutrient supply to the euphotic zone is achieved via a multistage mechanism: a diapycnal transfer of nutrients by small-scale turbulence to the euphotic zone, and an isopycnal stirring of nutrients by mesoscale eddies replenishing nutrients in the upper thermocline.